2008
DOI: 10.1038/npp.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Activation of Dopamine D1 Receptor Signaling and Inhibition of Class I/II Histone Deacetylase Induce Chromatin Remodeling in Reward Circuitry and Modulate Cocaine-Related Behaviors

Abstract: Chromatin remodeling, including histone modification, is involved in stimulant-induced gene expression and addiction behavior. To further explore the role of dopamine D 1 receptor signaling, we measured cocaine-related locomotor activity and place preference in mice pretreated for up to 10 days with the D 1 agonist SKF82958 and/or the histone deacetylase inhibitor (HDACi), sodium butyrate. Cotreatment with D 1 agonist and HDACi significantly enhanced cocaine-induced locomotor activity and place preference, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 59 publications
4
93
0
2
Order By: Relevance
“…These loci are the most likely sites in which HDACi and drugs of abuse interact to promote non-homeostatic neuroadaptations that underlie behavioral phenomena relevant to the context of addictive behavior, such as CPP and sensitization. This view is supported by a number of recent studies exploring changes in histone phosphorylation and acetylation at the promoters of Per1, c-fos, fosB, bdnf, and NK1R, among other genes, in response to the acute administration of HDACi or drugs of abuse (Kumar et al, 2005;Levine et al, 2005;Renthal et al, 2008aRenthal et al, , 2009Renthal et al, , 2007Russo et al, 2009;Schroeder et al, 2008). However, it should be also noted that HDACs deacetylate not only nucleosome histones, but also a much wider range of cellular proteins and can, therefore, also influence cell physiology and animal behavior through nongenomic mechanisms (Glozak et al, 2005;Spange et al, 2009).…”
Section: Discussionmentioning
confidence: 54%
“…These loci are the most likely sites in which HDACi and drugs of abuse interact to promote non-homeostatic neuroadaptations that underlie behavioral phenomena relevant to the context of addictive behavior, such as CPP and sensitization. This view is supported by a number of recent studies exploring changes in histone phosphorylation and acetylation at the promoters of Per1, c-fos, fosB, bdnf, and NK1R, among other genes, in response to the acute administration of HDACi or drugs of abuse (Kumar et al, 2005;Levine et al, 2005;Renthal et al, 2008aRenthal et al, , 2009Renthal et al, , 2007Russo et al, 2009;Schroeder et al, 2008). However, it should be also noted that HDACs deacetylate not only nucleosome histones, but also a much wider range of cellular proteins and can, therefore, also influence cell physiology and animal behavior through nongenomic mechanisms (Glozak et al, 2005;Spange et al, 2009).…”
Section: Discussionmentioning
confidence: 54%
“…Genetic inactivation of dopamine D1 but not D2 receptors inhibits histone acetylation (Darmopil et al 2009). When a D1 receptor agonist is given together with the HDAC inhibitor, the combination enhances cocaine-induced locomotor response and conditioned place preference (Schroeder et al 2008). The nicotine-induced activation of D1/ D5 receptors may lead to phosphorylation of CREB (Nestler 2004;Hyman et al 2006), which recruits the CREB-binding protein (CBP), a histone acetyl transferase that acetylates histones and consequently influences the transcription of genes and the modification of synapses (Kandel 2001;Guan et al 2002;Alarcon et al 2004;Levine et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, pharmacoepigenomics, or a drug's direct and indirect effects on chromatin structure and function, may perhaps in the future emerge as an interesting biomarker to predict treatment response, side effects or illuminate novel, hitherto unsuspected mechanisms of drug action. While this prediction is presently highly speculative, it is interesting to note that a wide range of psychoactive drugs, including dopamine receptor agonists (Schroeder et al, 2008), typical and atypical antipsychotics (Huang et al, 2007b;Li et al, 2004), and several mood-stabilizers, including lithium and valproate (Bredy et al, 2007;Dong et al, 2008;Kwon and Houpt, 2010), were shown to affect DNA methylation and/or histone acetylation, phosphorylation, and methylation in selected areas of the forebrain.…”
Section: Psychiatric Epigenetics In the Culture Dish?mentioning
confidence: 99%